On the impact of absorbed dose specification, tissue heterogeneities, and applicator heterogeneities on Monte Carlo‐based dosimetry of Ir‐192, Se‐75, and Yb‐169 in conventional and intensity‐modulated brachytherapy for the treatment of cervical cancer. Issue 5 (17th March 2021) - Morcos, Marc; Viswanathan, Akila N.; Enger, Shirin A.
Abstract : Purpose: The purpose of this study was to evaluate the impact of dose reporting schemes and tissue/applicator heterogeneities for 192 Ir‐, 75 Se‐, and 169 Yb‐based MRI‐guided conventional and intensity‐modulated brachytherapy. Methods and Materials: Treatment plans using a variety of dose reporting and tissue/applicator segmentation schemes were generated for a cohort (n = 10) of cervical cancer patients treated with 192 Ir‐based Venezia brachytherapy. Dose calculations were performed using RapidBrachyMCTPS, a Geant4‐based research Monte Carlo treatment planning system. Ultimately, five dose calculation scenarios were evaluated: (a) dose to water in water ( Dw, w ); (b) Dw, w taking the applicator material into consideration ( Dw, wApp ); (c) dose to water in medium ( Dw, m ); (d and e) dose to medium in medium with mass densities assigned either nominally per structure ( Dm, m (Nom) ) or voxel‐by‐voxel ( Dm, m ). Results: Ignoring the plastic Venezia applicator ( Dw, wApp ) overestimates Dm, m by up to 1% (average) with high energy source ( 192 Ir and 75 Se) and up to 2% with 169 Yb. Scoring dose to water ( Dw, wApp or Dw, m ) generally overestimates dose and this effect increases with decreasing photon energy. Reporting dose other than D m, m (or Dm, m Nom ) for 169 Yb‐based conventional and intensity‐modulated brachytherapy leads to a simultaneous overestimation (up to 4%) of CTVHR D90 and underestimation (up to 2%) of bladder D2cc due to a significant dip in the mass‐energy absorption ratios at the depths of nearby targets and OARs. Using a nominal mass‐density assignment per structure, rather than a CT‐derived voxel‐by‐voxel assignment for MRI‐guided brachytherapy, amounts to a dose error up to 1% for all radionuclides considered. Conclusions: The effects of the considered dose reporting schemes trend correspondingly between conventional and intensity‐modulated brachytherapy. In the absence of CT‐derived mass densities, MRI‐only‐based dosimetry can adequately approximate Dm, m by assigning nominal mass densities to structures. Tissue and applicator heterogeneities do not significantly impact dosimetry for 192 Ir and 75 Se, but do for 169 Yb; dose reporting must be explicitly defined since Dw, m and Dw, w may overstate the dosimetric benefits.